Methods of Forming Personality Tolerance Traits on the Basis of Communication Training - Norpolatovna, Yoldoshova Sarvinoz (European Journal of Life Safety and Stability (2660-9630), 2021)
Personality refers to an individual’s characteristics, style, behavior, mindset, attitude, his own unique way of perceiving things and seeing the world. Genetic factors, family backgrounds, varied cultures, environment, current situations play an imperative role in shaping one’s personality. The way you behave with others reflects your personality. An individual with a pleasing personality is appreciated and respected by all.